PENGARUH KOMPETENSI KARYAWAN, LINGKUNGAN KERJA, DAN KUALITAS PELAYANAN TERHADAP KINERJA KARYAWAN - Kumara Efrianti (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
This study aims to examine the influence of employees competence, job climate, and service quality to job performance. This study examined the influence of employees competence, job climate, and service quality to job performance. This research taken the sample from employees PDAM Tirta Barito Selatan, number of sample 60 respondent with purposive random sampling. The results of this research is employees competence , job climate, and service quality, has positive influence on job performance.